2022
DOI: 10.1002/pbc.29743
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional assessment and dietetic resource for children and young people with cancer in the United Kingdom

Louise Henry,
Susie Aldiss,
Faith Gibson
et al.

Abstract: Background: Both under-and overnutrition may have adverse impact on outcome of cancer in children and teenagers/young adults (CTYA). Previous studies confirm that screening for nutritional risk and detection of nutritional abnormality is inconsistently undertaken in practice. Methods:We undertook a survey of dietetic resource and nutritional assessment in CTYA principal treatment centres (PTC) in the United Kingdom. Responses were received from 95% children's and 69% TYA PTC.Results: Only 13/18 (72%) children'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Although arm anthropometry, according to abundant published data, assists in undernutrition recognition during pediatric cancer treatment, some studies have failed to present sufficient evidence in favor of its use in survivorship [ 49 ]. However, it is still evidently insufficiently utilized not only among our patients but also in other developed European countries, such as the United Kingdom [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although arm anthropometry, according to abundant published data, assists in undernutrition recognition during pediatric cancer treatment, some studies have failed to present sufficient evidence in favor of its use in survivorship [ 49 ]. However, it is still evidently insufficiently utilized not only among our patients but also in other developed European countries, such as the United Kingdom [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The content of the previously published cross-sectional survey of practice in the UK [10] was adapted to the New Zealand context; questions regarding nutrition intervention and complementary alternative medicine were added. The survey was converted to electronic format using REDCap electronic data capture tools hosted by the University of Auckland [11].…”
Section: Methodsmentioning
confidence: 99%
“…However, inconsistencies in the nutrition support available to children and with cancer are well documented. A recent study of Children's and Teenage and Young Adult (CTYA) principal treatment centres (PTC) within the United Kingdom found more than 50% of centres had limited access to dietetic resource and that there were variations in the use of nutritional screening tools, anthropometric measures, and general assessment of nutritional status [10]. These findings are similar to an earlier work conducted among member institutions of the Children's Oncology Group (COG) consortium in 2003; across institutions different indices were used to quantify nutrition status and when nutrition intervention was clinically indicated there was variability in which approach was adopted [11].…”
Section: Introductionmentioning
confidence: 99%
“…Often this is reflected in clinical practice and a recent survey of nutritional assessment in current prac- tice in the United Kingdom reported that the measurement of serum albumen was considered to be 'usually or sometimes' relevant in nutritional assessment by over 70% of paediatric and teenage young adult (TYA) tertiary treatment centres. 8 A study authored by Prasad and colleagues, 9 (SAM) by BMI-for-age Z-score < -3, or MUAC-for-age or TSFT-forage < 5th centile, or serum albumin < 3.2 g/dl. The number of patients diagnosed with SAM was higher when arm anthropometry was added to BMI (but there was only a minor advantage in including TSFT in addition to MUAC).…”
mentioning
confidence: 99%
“…Some previous studies have incorporated measurement of serum albumin as an additional criterion for identifying undernutrition but without clear justification of its benefit. Often this is reflected in clinical practice and a recent survey of nutritional assessment in current practice in the United Kingdom reported that the measurement of serum albumen was considered to be ‘usually or sometimes’ relevant in nutritional assessment by over 70% of paediatric and teenage young adult (TYA) tertiary treatment centres 8 …”
mentioning
confidence: 99%